Static Strength Analysis and Lug Support Design of Exhaust Stack in Mobile Power Plant Nias (25 MW) - MALIK SYARIATY (NIM : 13114143), ADLAN
PT. PLN cooperates with The Indonesian Government to execute the 35,000 MW program to fulfill one of the needs of Indonesian citizen. PT. PLN and Tripatra Engineers and Constructors collaborated to build a Diesel Power Plant (PLTD) with Tripatra chosen as the EPCC company. The goals of this final project is to analyze the static strength of structure and lug support of the exhaust stack based on the standards of the American Society of Civil Engineers 7-2016 to achieve desired resistance factor. Moreover, determine the critical areas that occur in the structure and specification of joints (bolts and welds). The methodology of this final project consists of literature study, collecting information about the models and specifications of the exhaust stack, silencer, and steel structure (data sheet), indetifying of various loading cases, discussion of mechanical division, finite element modeling, so that the results of the analysis are related to the strength of the structure. Based on the results of analysis, The maximum (von mises) stress of steel structure is 201,87 MPa at the connection hole which is a critical area of failure first with resistance factor is 0,80. The maximum (von-mises) stress of lug support is 186,05 MPa at the connection hole with resistance factor is 0,74. Bolts specification that used to connect between lug support and steel structure is property class 4.8 and welds specification that used to connect lug support with stack is E60xx.